An investigation of inactivation mechanisms of Bacillus amyloliquefaciens spores in non‐thermal plasma of ambient air. (30th July 2018) - Huang, Yaohua; Ye, Xiaofei P; Doona, Christopher J; Feeherry, Florence E; Radosevich, Mark; Wang, Siqun
Abstract: BACKGROUND: To utilize the potential of non‐thermal plasma technologies for food safety control and sanitation, the inactivation mechanisms of Bacillus amyloliquefaciens spores by non‐thermal plasma of ambient air (NTP‐AA) were investigated using scanning electron microscopy, atomic force microscopy, attenuated total reflectance Fourier transform infrared spectroscopy with chemometric analysis and proton nuclear magnetic resonance spectroscopy, aiming to probe both the morphological and biochemical changes occurring in spores during the kinetic inactivation process. RESULTS: Kinetic analysis indicates that there is no intrinsic D ‐value (i.e. time required to inactivate 90% of the spores) in spore inactivation by NTP‐AA because we observed non‐linear (biphasic) inactivation kinetics and, in addition, the inactivation rate depended on the initial spore concentration and how the spores were exposed to the reactive species in the NTP‐AA. The presence of suitable amount of water in the NTP‐AA field accelerates spore inactivation. CONCLUSION: Progressive erosion of spore surface by NTP‐AA with ensuing or concomitant biochemical damage, which includes the alteration of structural proteins, internal lipids and the loss of dipicolinic acid content from the spore core, represent the main mechanisms of inactivation, and there is evidence that reactive NTP‐AA species could penetrate the cortex and reach the core of spores to cause damage. © 2018 Society of Chemical Industry